Higher Perceived Stress Increases the Subjective Reporting of ADHD: A Sample of Medical Students - Gülsüm Akdeniz; Elif Akçay; Gulsen Yilmaz; Pınar Özışık (Genel Tıp Dergisi)
This study aimed to evaluate the subjective Attention-Deficit/Hyperactivity Disorder (ADHD) symptoms with self-reported ratings and objective neurocognitive tests among medical students. Also, we examined to identify the psychological factors that predict ADHD reporting among medical students. Medical students (N=57) completed self-report questionnaires, and neurocognitive tests were conducted for attention measures. Participants had a mean age of 20.3 years, and 69.0% were female. High levels of perceived stress, state-trait anxiety, and current and childhood ADHD symptoms were possible risk factors; however, only higher perceived stress was a risk factor for the possibility of reporting themselves as ADHD in medical school students [odds ratio [OR] =1.184, 95% confidence interval [CI] = [1.015; 1.381]]. Higher perceived stress levels, the more reported ADHD subjectively in medical students. Objective attention measures had no impact on reporting ADHD subjectively. Screening for perceived stress is necessary for medical students, especially those with subjective ADHD symptoms.